2003
DOI: 10.1002/chin.200323198
|View full text |Cite
|
Sign up to set email alerts
|

Naucleamides A—E, New Monoterpene Indole Alkaloids from Nauclea latifolia.

Abstract: Alkaloids Alkaloids U 0600Naucleamides A-E, New Monoterpene Indole Alkaloids from Nauclea latifolia.-Together with three known substances the novel title compounds such as (I)-(IV), named naucleamides A-E are isolated from the bark and wood of the title plant. -(SHIGEMORI, H.; KAGATA, T.; ISHIYAMA, H.; MORAH, F.; OHSAKI, A.; KOBAYASHI*, J.; Chem. Pharm. Bull. 51 (2003) 1, 58-61; Grad. Sch. Pharm. Sci., Hokkaido Univ., Sapporo 060, Japan; Eng.) -K. Schneider 23-198

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Phytochemical investigations on Nauclea species have revealed the presence of terpenes and/or secoridoids (Adebowale et al, 1983;Lamidi et al, 1995a), quinovic acid and derivatives (Lamidi et al, 1995b), saponins (Lamidi et al, 1997) and alkaloids (Hotellier et al, 1979;Lin et al, 1985, 1989: Zeches et al, 1985Deeni and Hussain, 1991;Erdelmeier et al, 1991;Anam, 1997;Zhang et al, 2001;Ngnokam et al, 2003;Shigemori et al, 2003;Takayama et al, 2003). All antimalarial activity previously reported in Nauclea species has been attributed to the presence of saponins (Lamidi et al, 1996) or alkaloids (Traore-Keita et al, 2000).…”
Section: Nauclea Pobeguiniimentioning
confidence: 92%
“…Phytochemical investigations on Nauclea species have revealed the presence of terpenes and/or secoridoids (Adebowale et al, 1983;Lamidi et al, 1995a), quinovic acid and derivatives (Lamidi et al, 1995b), saponins (Lamidi et al, 1997) and alkaloids (Hotellier et al, 1979;Lin et al, 1985, 1989: Zeches et al, 1985Deeni and Hussain, 1991;Erdelmeier et al, 1991;Anam, 1997;Zhang et al, 2001;Ngnokam et al, 2003;Shigemori et al, 2003;Takayama et al, 2003). All antimalarial activity previously reported in Nauclea species has been attributed to the presence of saponins (Lamidi et al, 1996) or alkaloids (Traore-Keita et al, 2000).…”
Section: Nauclea Pobeguiniimentioning
confidence: 92%
“…The studied plant did not fell short of expectation in this regard as the quantitative phytochemical screening revealed the presence of most of these important bioactive constituents. Alkaloids, flavonoid, terpenoids, saponins and glycosides have all been implicated to posses antiplasmodial activity [22,23] among other beneficial effects. Alkaloids are well recognized bioactive compounds with potent therapeutic activity, they are also, the parent compounds for synthetic products like chloroquine [7].…”
Section: Discussionmentioning
confidence: 99%
“…The above data revealed that the structure of 1 was similar to that of naucleamide A (2) [6]. The only significant difference was the presence of one methylene carbon signal at δ 36.6 instead of one methine carbon at δ 48.8 and one methylene carbon signal at δ 62.9 in naucleamide A (2) [6]. Detailed analysis of spectroscopic data revealed that the hydroxymethyl at C-16 in naucleamide A ( 2 2.…”
mentioning
confidence: 82%
“…Phytochemical studies on this genus have led to the isolation of various skeletal types of monoterpenoid indole alkaloids with antitumor activities, which have attracted pharmacologists' attention [2][3][4][5]. As a part of our ongoing research into structurally and biologically interesting alkaloids from tropical medicinal plants in China, a chemical investigation of O. borbonica was thus undertaken and led to the isolation and characterization of a new monoterpenoid indole alkaloid, ochroborbone (1), together with five known alkaloids, naucleamide A (2) [6], corynantheol (3) [7], sitsirikine (4) [8], 19, 20-dihydroisositsirikine (5) [9], and 10hydroxy-19, 20-dihydroisositsirikine (6) [10]. Among them, ochroborbone (1) is a rare C17-nor monoterpenoid indole alkaloid, and the known compounds (2-6) were isolated from Ochrosia for the first time.…”
mentioning
confidence: 99%